Peculiarities of Cryopreservation Effect on Functional Potential of Fetal Liver Hemopoietic Stem Cells of Various Gestation Terms - Goltsev, A. N.; Dubrava, T. G.; Ostankova, L. V.; Grischenko, V. I.; Yampolskaya, E. Ye.; Ostankov, M. V.; Bondarovich, N. A.; Sirous, M. A. (Problems of Cryobiology and Cryomedicine, 2009)
The capability of cryopreservation to modify structural and functional status of bioobject, including fetal liver cells (FLCs), may be applied for cell and tissue therapy optimisation. The efficiency of FLCs application is determined by the presence in them of a wide spectrum of cell populations, including hemopoietic stem cells. There has been established a change in phenotypic and functional characteristics of FLCs with gestation term prolongation, manifesting in a decrease in their colony-forming potential, CD34+ number and a simultaneous increase in Mac-1+ and LFA-1+ cells. Cryopreservation was shown as capable for a selective enrichment of 18 gestation day’s FLCs by hemopoietic precursors with a high proliferative potential. This fact may be determining one in their therapeutic effect manifestation.